Effect of strain and sex of bird on carcass and fat yield of foraging slow-growing chickens - MUTIBVU, TONDERAI; CHIMONYO, MICHAEL; HALIMANI, TINYIKO E (The Indian Journal of Animal Sciences, 2017)
Meat and fat yield influence the profitability of modern commercial poultry production. This study sought to determine the effect of strain and sex on carcass and fat yield of three slow-growing chicken strains reared in open and closed pens. Two hundred and fifty-eight, 20-week old PK, OV and NN chickens, weighing 1710±308.8 g, were allocated to 4 paddocks of Chloris gayana and 4 pens in a poultry house. Final body weight (BW), carcass (CW), dressed (DW) weight, cut, abdominal fat pad (AFP) yield and giblet weights were determined. As a result of this study, strain did not affect BW but influenced back, pancreas, gizzard, neck, crop and AFP weight. Sex of bird influenced BW and males were significantly heavier, yielding heavier cuts and pancreases but lighter AFP than females. It was concluded that foraging males yield heavier cuts and females are fattier than foraging males of the same strain. Evaluating fatty acid composition of meat from foraging birds could help quantify risk associated with consumption of meat from foraging slow-growing chickens.